(untitled) (Development Service Industry Management, 2024)
The logistics industry today faces numerous challenges, such as the complexity of managing supply chains, insufficient transparency of processes, difficulties with tracking goods and ensuring their authenticity. These problems not only reduce the efficiency of logistics and customs processes, but also lead to increased costs and a decrease in the level of trust among the "players" of the market. With the development of distributed ledger technologies (DRL), in particular blockchain, new opportunities for solving these problems have appeared. TRRs offer a safe, transparent and immutable way of storing data, which makes them attractive for use in the process of identification of goods, in the formation of logistics operations and in customs affairs. The use of TPR can significantly improve the process of tracking goods in the supply chain, ensure the authenticity of goods, simplify the actions of regulatory authorities and reduce the risk of fraud. However, despite significant interest in this technology, their large-scale implementation faces a number of challenges that require detailed study and resolution. The application of TPR in logistics and identification of goods is important not only from a theoretical point of view, but also has a significant practical impact. Scientific study of this topic, implementation of standardization will help to develop new methods and use innovative tools to increase the efficiency of logistics processes. The practical implementation of the results of TRR research can contribute to increasing the speed of information service of logistics processes and customs procedures, the competitiveness of enterprises, reducing costs and improving the quality of customer service. The purpose of the study is theoretical and applied justification of the relevance of using distributed ledger technologies in the development of modern business systems. Distributed ledger technologies date back to 1991, with an article by Stuart Haber and W Scott Stornetta, which was devoted to solving the important question of "how to time-sign an electronic document." Subsequently, in 2008, the practical implementation of TRR took shape in the form of a decentralized system of digital payments (Bitcoin). Simplified, the TRR can be presented as a sequentially noted collection (chain) of transactions created by users of the registry. TPP works using a network of independent nodes (nodes) that store copies of the registry. When a user wants to make changes to the registry, they send a transaction to other nodes. Nodes use a "consensus mechanism" to determine if a transaction is legitimate. If the transaction is legitimate, it is added to the registry. Transactions are grouped into blocks, which are then encrypted and combined with previous blocks. This creates a chain of blocks, which is also called a blockchain (Blockhain). The use of TPP has a number of advantages over traditional centralized systems. Copies of the distributed ledger chain are maintained by different independent users of the ledger (nodes) and are cryptographically protected. The concept involves the absence of a centralized control body, so there is no single "point of failure". So, subject to certain conditions, it is not possible to individually delete or change the data contained in the registry. The security of using TPP consists in the use of cryptography to protect data. Each block is connected to the previous one through a hash function, which makes it almost impossible to change already recorded blocks. This ensures a high level of security and data integrity. Transparency of use TPP is a transparent system in which all participants can view records and transactions in real time. This makes processes more transparent for all parties interacting in the network. The efficiency and speed of using TPP can speed up the processes of exchanging data, electronic assets and other transactions, as they occur without intermediaries and with fewer intermediate steps. Cost reduction consists in the absence of intermediaries and a reduction in the level of bureaucratic procedures, which can significantly reduce costs for various business processes. The cost of transactions can be lower, the infrastructure becomes faster and more efficient. Reliability and recoverability lies in the use of a distributed ledger, which is fault-tolerant because each block is stored on different network nodes. If one node fails, the others will continue to serve the network, ensuring a high level of availability. The TPP distributed ledger information technology is a relatively new technology, but has a synergistic combination of properties that was previously unattainable when using "traditional database" technologies. The possibility and expediency of using TRR in various economic sectors is still being studied by individual specialists and commercial companies. The perceived potential and significant benefits of using TPP are clear, but there are certain limitations that need to be overcome. The article offers an example of a template for the implementation of a digital product passport, indicates the feasibility of using such a passport in logistics and customs affairs, suggests a method of overcoming the problem of "transparency" of distributed registers by storing sensitive information in the register in an encrypted form. The current state of development of distributed ledger technologies (DRT) and examples of their implementation by commercial companies allow for further scientific and applied work on the improvement of such technologies, their standardization, and the legal legalization of these processes.